Embryotoxicity and hair cell toxicity of silver nanoparticles in zebrafish embryos. (April 2016) - Yoo, Myung Hoon; Rah, Yoon Chan; Choi, June; Park, Saemi; Park, Hae-Chul; Oh, Kyoung Ho; Lee, Seung Hoon; Kwon, Soon-Young
Abstract: Objectives: The purpose of the present study was to evaluate silver nanoparticles (AgNP)-induced embryotoxicity and hair cell toxicity during zebrafish development. Methods: We exposed zebrafish embryos to various AgNP concentrations (30, 60, 120, and 240 nM) and evaluated embryotoxicity at 72 h and ototoxicity at 120 h. Embryotoxicity parameters including abnormal morphology, mortality, hatching rate, and heart rate were investigated. Hair cells within four neuromasts were evaluated. In the present study, the average number of hair cells of zebrafish exposed to AgNP was compared with that of an unexposed control group. Results: The hatching rate was not significantly different between groups (control: 90%; AgNP 240 nM: 89%). The control group showed 2% mortality and 0% teratogenicity, while the AgNP 240 nM group showed increased mortality (11%) and teratogenicity (15%) at 72 h ( n  = 100). The heart rate of AgNP-exposed embryos tended to be lower than that of the control group ( n  = 38). Furthermore, AgNP induced apoptotic hair cell damage in the neuromasts (control: 50.7 ± 7.4 cells; 240 nM AgNP: 41.1 ± 6.3 cells, n  = 23). TUNEL positive cell counts increased significantly as AgNP concentration increases ( p  < 0.001, n  = 20 in each group). Conclusions: The results of this study indicate that AgNP exposure causes embryotoxicity and hair cell toxicity in zebrafish embryos.